Additive manufacturing of magnetic polymer phantoms for magnetic particle imaging (Transactions on Additive Manufacturing Meets Medicine, 2019)
Motivation: Magnetic nanoparticles (MNP) are a class of nanomaterials with outstanding features for biomedical applications. A novel diagnostic method for the visualization of the spatial distribution of MNP is magnetic particle imaging (MPI). Long-term stable phantoms with defined geometry and MNP content are mandatory for resolution determination, for cross-comparison of MPI scanners, or as fiducial markers to verify the spatial position of the body under analysis. The aim of our work was to produce stable and homogeneous magnetic composites consisting of photopolymers with embedded MNP.Materials and Methods: A fast and cost-effective way to manufacture phantoms is generative printing, commonly called 3D-printing. This additive technique allows manufacturing of customized parts with complex shapes out of specific photopolymers solidifying layer by layer under ultraviolet radiation. We produced homogeneous magnetic composites consisting of photopolymers (R05 red, E-Shell) with embedded MNP (EMG 700 Ferrtec). For the process development a systematic quality evaluation was performed, which fully considers the magnetic properties, the homogenization procedure, the polymer cross-linking, the mixture ratio, and the subsequent analysis of the resulting parts (structurability, magnetism).Results and Discussion: We found a linear scaling of the magnetic moment with nominal MNP amount as well as stable magnetic properties of 3D printed magnetic composites. This enabled the production of MPI phantoms with defined MPI signaling at different concentrations. Additionally, the documented long-term stability of the phantoms made them suitable for calibration purposes, quality assurance as well as round robin test phantoms in MPI. Furthermore, the processability significantly improved for magnetic composites compared to the photopolymer, alone. Finally, the magnetic composites were properly visualized by MPI which qualifies 3D printed magnetic composites for future MPI applications.Conclusion: With the developed procedure, we advanced the characterization of MPI scanners by providing defined, long-term stable magnetic composite phantoms that could also resemble body-like parts.